INNOVATIVE APPROACHES TO ORGANIZING GYMNASTICS-BASED PHYSICAL EDUCATION ACTIVITIES IN PRESCHOOL INSTITUTIONS - Kosimov Bekzod Zoirovich (International Journal of Literature and Language Studies, 2026)
This paper explores innovative pedagogical approaches to organizing gymnastics-based physical education activities in preschool institutions. The study focuses on the integration of modern teaching technologies, game-based learning strategies, interactive gymnastics exercises, and digital tools to enhance children’s physical activity and engagement. The research highlights how innovative methods contribute to improving motor development, motivation, participation levels, and overall physical fitness in early childhood education settings.